2006
DOI: 10.1097/01.shk.0000223128.79759.3d
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatidylinositol 3 Kinase Pathway Regulates Tolerance to Lipopolysaccharide and Priming Responses to Staphylococcus Aureus and Lipopolysaccharide

Abstract: Our previous studies have demonstrated that although LPS and Staphylococcus aureus induce homologous tolerance, they induce priming to each other instead of cross-tolerance. The phosphatidylinositol 3 (PI3) kinase pathway has been implicated in microbial signaling and inflammatory gene expression regulation. We hypothesized that LPS or S. aureus induced tolerance and priming responses to each other are PI3 kinase pathway-dependent. CD1 mice received intraperitoneal injections of 1% Biogel and were treated intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The decreased secretion of mediators associated with the tolerance phenomenon has been linked to alterations in signal events (14,28). Phosphatidylinositol‐3′‐kinase, an enzyme complex, regulates a pathway involved in the expression of various lipopolysaccharide‐induced inflammatory genes and lipopolysaccharide tolerance (28,29). It behaves as an early inhibitor of Toll‐like receptor signaling (30).…”
Section: Resultsmentioning
confidence: 99%
“…The decreased secretion of mediators associated with the tolerance phenomenon has been linked to alterations in signal events (14,28). Phosphatidylinositol‐3′‐kinase, an enzyme complex, regulates a pathway involved in the expression of various lipopolysaccharide‐induced inflammatory genes and lipopolysaccharide tolerance (28,29). It behaves as an early inhibitor of Toll‐like receptor signaling (30).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with our observations, there have been increasing studies indicating that PI3K/AKT pathway is essential for LPS-induced tolerance. For example, it has been reported that blockade of PI3K with its inhibitor wortmannin reversed in vivo tolerance in LPS-pretreated mice ( 48 , 49 ). For another example, results from Pik3r1 −/− -deficient mice (PI3K activity reduced) and PTEN −/− mice (AKT activity enhanced) demonstrated that PI3K/AKT pathway negatively regulated LPS signaling in macrophages and endotoxemic mice ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Guha and Mackman have reported that activation of the PI3 kinase/Akt signaling pathway limits the pro-inflammatory effects of LPS in cultured monocytes (17). Our recent studies demonstrated PI3 kinase inhibitor, wortmannin, and LY294002 abolished the protective effect of endotoxin tolerance (41). Numerous studies have demonstrated that LPA can activate the PI3 kinase signaling pathway (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%